LITERASI INFORMASI KECANTIKAN DI KALANGAN PENGGUNA FEMALE DAILY NETWORK - Derma Ekaputri, Sarah; Meutia Karolina, Cut; N. Abdullah, Nisa (BACA: Jurnal Dokumentasi dan Informasi, 2020)
The presence of Female Daily Network is giving convenience in accessing and sharing various information about the beauty. This research aims to know the information literacy among the users of Female Daily Network. This research uses descriptive quantitatives method. This research shows that information literation about beauty amongst users can be categorized as high with the average score of 75,95%. It indicates that this platform can fulfill the needs of beauty information by users. The majority of users consist of productive female adolescents who really need beauty information that supports their needs of daily life appearance, as well as to overcome various beauty problems.